Role of Rab GDP dissociation inhibitor α in regulating plasticity of hippocampal neurotransmission - Ishizaki, Hiroyoshi (The National Academy of Sciences, 2000)
Rab GDP dissociation inhibitor α (Rab GDIα) is a regulator of the Rab small G proteins implicated in neurotransmission, and mutations of Rab GDIα cause human X-linked mental retardation associated with epileptic seizures. In Rab GDIα-deficient mice, synaptic potentials in the CA1 region of the hippocampus displayed larger enhancement during repetitive stimulation, which was apparently opposite to the phenotype of Rab3A-deficient mice. Furthermore, the Rab GDIα-deficient mice showed hypersensitivity to bicuculline, an inducer of epileptic seizures. These results suggest that Rab GDIα plays a specialized role in Rab3A recycling to suppress hyperexcitability via modulation of presynaptic forms of plasticity.